2020
DOI: 10.1002/mabi.202000317
|View full text |Cite
|
Sign up to set email alerts
|

Designing Gelatin Methacryloyl (GelMA)‐Based Bioinks for Visible Light Stereolithographic 3D Biofabrication

Abstract: Bioinks play a key role in determining the capability of the biofabricatoin processes and the resolution of the printed constructs. Excellent biocompatibility, tunable physical properties, and ease of chemical or biological modifications of gelatin methacryloyl (GelMA) have made it an attractive choice as bioinks for biomanufacturing of various tissues or organs. However, the current preparation methods for GelMA‐based bioinks lack the ability to tailor their physical properties for desired bioprinting methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 68 publications
0
52
0
Order By: Relevance
“…The possibility to perfuse these structures was proven via the infusion of a colored dye solution, and the smallest tubular feature within the complex Willis vessel network was measured to be 183 ​± ​25 ​μm. Overall, the possibility to generate such high resolution, convoluted structures via vat polymerization printing has not been achieved with other gels with low compressive properties, not even when utilizing other types of low viscosity gelatins obtained from the partial degradation of the polymer backbone [ 65 ]. It should be noted that, in the proof-of-concept prints reported in our study, perfusion was demonstrated via manual injection, recent reports in the literature highlight elegant strategies for enabling the connection of hydrogel-based constructs to fluidic tubing and circuits, which could be applied to automate fluid flow [ 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…The possibility to perfuse these structures was proven via the infusion of a colored dye solution, and the smallest tubular feature within the complex Willis vessel network was measured to be 183 ​± ​25 ​μm. Overall, the possibility to generate such high resolution, convoluted structures via vat polymerization printing has not been achieved with other gels with low compressive properties, not even when utilizing other types of low viscosity gelatins obtained from the partial degradation of the polymer backbone [ 65 ]. It should be noted that, in the proof-of-concept prints reported in our study, perfusion was demonstrated via manual injection, recent reports in the literature highlight elegant strategies for enabling the connection of hydrogel-based constructs to fluidic tubing and circuits, which could be applied to automate fluid flow [ 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…Hydrogels are high water content materials and one of the few biomaterials that can be used to fabricate extracellular matrix (ECM) mimicking scaffolds [ 11 , 12 ]. Moreover, in addition to being highly biocompatible, hydrogels possess an advantageous physical and biological tunability, and desirable robustness in biofabrication [ [13] , [14] , [15] ]. Although some synthetic materials have been shown to be less prone to evoke an immune response [ 16 ], naturally-derived crosslinked polymeric networks are preferred to avoid the potential risk of inflammatory and immunological responses induced by synthetic polymeric materials [ [17] , [18] , [19] , [20] , [21] , [22] ].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the 20 ME MeSDVC may not be suitable for implanting into a cartilage defect (i.e., can leak out before crosslinking). However, it is worthwhile to note that such low-viscosity precursors may be suitable for other types of bioprinting (e.g., digital light processing, inkjet) [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%